2018
DOI: 10.1111/bjd.16442
|View full text |Cite
|
Sign up to set email alerts
|

Pilocarpine and artificial saliva for the treatment of xerostomia and xerophthalmia in Sjögren syndrome: a double-blind randomized controlled trial

Abstract: Pilocarpine is more effective than artificial saliva for enhancing salivary and lacrimal secretion in patients with SS. This is the first study to compare the efficacy of pilocarpine and artificial saliva for the treatment of xerostomia and xerophthalmia in SS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 18 publications
1
37
0
6
Order By: Relevance
“…Cifuentes, Barrio‐Diaz, and Vera‐Kellet () observed in a clinical trial at low risk of bias a significantly higher unstimulated salivary flow rate at 12 weeks in patients taking 10 drops of pilocarpine (5 mg) three times a day versus 10 drops of artificial saliva (oral Schirmer test: 0.924 cm/min vs. 0.297 cm/min; p < 0.05). These results suggest a large effect size but unclear clinical significance.…”
Section: Resultsmentioning
confidence: 99%
“…Cifuentes, Barrio‐Diaz, and Vera‐Kellet () observed in a clinical trial at low risk of bias a significantly higher unstimulated salivary flow rate at 12 weeks in patients taking 10 drops of pilocarpine (5 mg) three times a day versus 10 drops of artificial saliva (oral Schirmer test: 0.924 cm/min vs. 0.297 cm/min; p < 0.05). These results suggest a large effect size but unclear clinical significance.…”
Section: Resultsmentioning
confidence: 99%
“…The only symptomatic treatment that has clearly shown its efficacy on pSS is pilocarpine, but its level of evidence varies and it is related to the residual glandular parenchyma (Noaiseh et al, ; Papas et al, ; Seror & Mariette, ; Cifuentes et al, , Watanabe et al, , Fernández‐Martínez et al, , Al Hamad et al, ). Common side effects of pilocarpine are sialorrhoea, sweating, urinary frequency, bitter taste, stomatodynia, sickness, sore throat, gastritis and dyspnoea (Cifuentes et al, ; Fernández‐Martínez et al, ). Thus, the use of pilocarpine is contraindicated in patients with chronic illnesses such as cardiovascular disease, kidney failure, asthma and other chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies (Cifuentes et al, ) that obtained great xerostomia improvement with the use of pilocarpine in pSS, and they observed that non‐responders have a greater duration of the pSS disease. In this study (Cifuentes et al, ), mean duration of the disease was about 22.16–23.28 months. In our study, the duration of the disease was greater 139.38 ± 89.47 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations